OP0314 B cell phenotype and function in the synovium of acpa+ and acpa- rheumatoid arthritispatients. (12th June 2018) - Floudas, A.; Biniecka, M.; Low, C.; Veale, D.J.; Fearon, U.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease of unknown and complex etiology with severe detrimental effects for the patient's quality of life. While rheumatoid factors (RF) and anti-citrulinated protein antibodies (ACPA) have been used extensively for the diagnosis of RA, no clear mechanism of action towards disease pathogenesis and progression has been identified. Importantly, both seropositive and seronegative RA patients experience significant improvement in disease severity following B cell depletion. Therefore, we hypothesised that B cells have a central role in ACPA + and ACPA - RA irrespective of their capacity to produce auto-antibodies. Objectives: The characterisation of B and T cell populations in the peripheral blood and synovium of ACPA +, ACPA - and arthralgia patients. The identification of non-antibody mediated B cell function under the hypoxic conditions of the inflamed joint. Methods: Peripheral blood, synovial fluid and tissue was obtained from ACPA +, ACPA - and arthralgia patients. Following enzyme digestion of the tissue, several 15-colour panels were used for the flow cytometric analysis of T and B cell populations of ACPA +, ACPA - and arthralgia patients compared to healthy subjects. Activation and function of healthy, sorted B cells, cultured in vitro and stimulated by CD40 and BCR mediated signals under normoxic (21% O2 ) and hypoxic (1% O2 ) conditions was examined. Results: Pro-inflammatory cytokine production by peripheral blood CD4 + T cells is not significantly different between ACPA +, ACPA - and arthralgia patients when compared to healthy controls. However, a significant reduction in CD27 + switched memory B cells was observed between healthy subjects and APCA + RA patients. The aforementioned decrease in memory B cells is potentially a result of increased susceptibility to FAS induced apoptosis since healthy B cells cultured with RA patient plasma showed increased activation, CD80/CD86 and FAS expression. In the synovial fluid and synovial tissue, CD4 T cell pro-inflammatory cytokine production was increased when compared to peripheral blood CD4 T cells. Interestingly, ACPA - RA patient CD4 + T cells produced reduced amounts of pro-inflammatory cytokines when compared to ACPA + RA patient CD4 + T cells. Despite accumulation of switched and double negative (DN) memory B cells in the synovial fluid and tissue, compared to peripheral blood, no differences in synovial B cell subpopulation composition between ACPA + and ACPA - RA patients was observed. Interestingly, sorted B cells from healthy subjects showed increased sensitivity to in vitro stimulation with increased expression of CD80 and CD86 when cultured under hypoxic conditions, while co-culture with RA patient synovial fibroblasts did not enhance this effect. Conclusions: The increased capacity of ACPA + compared to ACPA - RA patient synovial CD4 + T cells to produce pro-inflammatory cytokines, could be responsible for the more severe disease progression of ACPA + compared to ACPA - RA. The accumulation of memory B cells in both ACPA + and ACPA - RA, underlines a common, antibody independent, contribution of B cells in synovial inflammation. While B cell activation under hypoxic conditions and increased CD80/CD86 expression is potentially an important mediator for the emergence of auto-reactive T cells and disease progression in RA. Disclosure of Interest: None declared